Trends and correlates of male participation in maternal healthcare in a rural district in Ghana - Gilbert Abotisem Abiiro; Emmanuel Kofi Gyan; Kennedy A. Alatinga; Roger A. Atinga (Scientific African, 2022)
Male participation in maternal healthcare is important for better-quality maternal health outcomes. This study assessed the trends and correlates of male participation in antenatal care (ANC), delivery and postnatal care (PNC) in the Jaman North District of Ghana. Longitudinal data from 2012 to 2019 on male involvement in maternal healthcare were extracted from health records. A cross-sectional survey was administered to a stratified random sample of 318 mothers, who registered for PNC in 2020. Line graphs were used to illustrate the trends of male participation, and binary logistic regression analysis used to identify the correlates of male participation. The results show consistently low rates of male participation in maternal healthcare, with relatively higher participation rates for delivery compared to ANC and PNC within 2012–2019. The prevalence of male participation in the survey was 52.52% for delivery, 31.76% for PNC and 23.58% for ANC. Male participation in ANC was associated with a higher likelihood (p < 0.05) for women aged ≤ 31years, married, educated, employed or had pregnancy-related complications, and a lower likelihood for those who stayed ≤ 3years with their partners (AOR= 0.171; 95%CI 0.059–0.490) or had ≤ 2 children (AOR= 0.108; 95%CI: 0.019–0.608). Christianity (AOR=2.708; 95% CI of 1.296–5.660), motorcycle transport (AOR=4.340; 95%CI: 2.386–7.898) and pregnancy-related complications (AOR=1.823; 95% CI: 1.002–3.315) were associated with a high likelihood of male participation in delivery. Polygyny (AOR=0.343; 95%CI: 0.139–0.848), ≤ 2 children (AOR=0.240; 95%CI 0.081–0 .715); and higher income (AOR=2.114; 95%CI: 1.202–3.718), were associated with low and high likelihoods of male participation in PNC, respectively. Given the low rates of male participation in maternal healthcare, community-level interventions such as drama and durbars on the importance of male participation should be targeted at the less educated, Muslims, newly married, low income and polygynous homes.